Improvements in knee biomechanics during walking are associated with increased physical activity after total knee arthroplasty. Issue 12 (14th July 2015) - Arnold, John B.; Mackintosh, Shylie; Olds, Timothy S.; Jones, Sara; Thewlis, Dominic
ABSTRACT: Total knee arthroplasty (TKA) in people with knee osteoarthritis increases knee‐specific and general physical function, but it has not been established if there is a relationship between changes in these elements of functional ability. This study investigated changes and relationships between knee biomechanics during walking, physical activity, and use of time after TKA. Fifteen people awaiting TKA underwent 3D gait analysis before and six months after surgery. Physical activity and use of time were determined in free‐living conditions from a high resolution 24‐h activity recall. After surgery, participants displayed significant improvements in sagittal plane knee biomechanics and improved their physical activity profiles, standing for 105 more minutes ( p  = 0.001) and performing 64 min more inside chores on average per day ( p  = 0.008). Changes in sagittal plane knee range of motion (ROM) and peak knee flexion positively correlated with changes in total daily energy expenditure, time spent undertaking moderate to vigorous physical activity, inside chores and passive transport ( r  = 0.52–0.66, p  = 0.005–0.047). Restoration of knee function occurs in parallel and is associated with improvements in physical activity and use of time after TKA. Increased functional knee ROM is required to support improvements in total and context specific physical activity. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1818–1825, 2015.